Kinetics and mechanism of H and OH electrosorption on faceted (100) Pt electrodes in acid solutions - Bilmes, S. A. (1987)
The multiplicity of voltammetric peaks related to H-adatom and OH electroadsorption/electrodesorption reactions on faceted (100) Pt in 1 M H2SO4 and 0.5 M HClO4 are investigated at different temperatures by using linear sweep voltammetry with triangular modulation covering a relatively large frequency range of the modulating signal. The voltammetric multiplicity related to H-adatom reactions in acid electrolytes is sensitive to both the surface structure and the structure of the solution side of the edl. The kinetics of the reactions are apparently influenced in a cooperative way by the water-H-adatom-an-ion ensemble formed at each site of a particular crystallographic plane. The main three reactions exhibit different relaxation time constants from which one can infer that the process occurring in the potential range presumably closer to the potential of zero charge is the slowest one. Anion adsorption produces a surface energy leveling effect and changes the kinetics of the electrochemical reactions. The H-adatom reactions can be interpreted through a formalism comprising the surface diffusion of H-adatom among different adsorption sites followed by a relatively fast electrochemical step involving only one kind of H-adatom. Data obtained for the OH-adsorbed reaction show, in principle, the same trend as that of the H-adatom reactions, although in this respect more extensive data are required.